Fine mapping of a quantitative trait locus for spikelet number per panicle in a new plant type rice and evaluation of a near-isogenic line for grain productivity - Sasaki, Kazuhiro; Fujita, Daisuke; Koide, Yohei; Lumanglas, Patrick D.; Gannaban, Ritchel B.; Tagle, Analiza G.; Obara, Mitsuhiro; Fukuta, Yoshimichi; Kobayashi, Nobuya; Ishimaru, Tsutomu (Oxford University Press, 2017)
Total spikelet number per panicle (TSN) is one of the determinants of grain productivity in rice (Oryza sativa L.). In this study, we attempted to detect quantitative trait loci (QTLs) for TSN in the introgression lines with high TSN, derived from the cross of Indica Group variety IR 64 with new plant type lines. Two QTLs were detected on the long arm of chromosome 12: qTSN12.1 in the BC4F2 population of YTH63/IR 64 and qTSN12.2 in the BC4F3 population of YTH83/IR 64. TSN of the main tiller was significantly higher in near-isogenic lines (NILs) for qTSN12.1 (IR 64-NIL1; 188.6) and for qTSN12.2 (IR 64-NIL12; 199.4) than in IR 64 (141.2), owing to a significant increase in both primary and secondary branch numbers. These results suggest the critical function of these QTLs in the promotion of rachis branching at the panicle formation stage. Fine mapping of qTSN12.2 revealed six candidate genes in a 92-kb region of the Nipponbare reference genome sequence between flanking markers RM28746 and RM28753. Detailed phenotyping of agronomic traits of IR 64-NIL12 carrying qTSN12.2 showed drastic changes in plant architecture: this line had lower panicle number, longer culm, and longer and wider leaves compared with IR 64. Percentage of fertility and 1000-grain weight tended to be greater, and grain yield per square meter was also greater in IR 64-NIL12 than in IR 64. The newly identified QTLs will be useful for genetic improvement of the yield potential of Indica Group varieties. The markers tightly linked to qTSN12.2 are available for marker-assisted breeding